Analisis Kualitas Jaringan 4G LTE: Studi Kasus antara Telkomsel dan Tri Melalui Metode Drive Test - Afrizal Yuhanef; Dikky Chandra; Isnurisi Isnurisi (Universitas Muhammadiyah Surakarta, 2023)
Nanggalo Subdistrict is one of the sub-districts located in the city of Padang, West Sumatra Province. The advantages of data transfer speeds owned by 4G Long Term Evolution (LTE) make telecommunications operators compete with each other to provide the best service quality, but there is still a decrease in network quality in the Nanggalo District area at Telkomsel and Tri operators. So it is necessary to do a drive test to measure and find out the network quality of the two operators. Measuring the quality of a 4G network with RSRP, SINR, and Throughput parameters and how to retrieve data is a benchmark. The software used is TEMS Pocket to take measurement data during the drive test, TEMS Discovery Software to process the data of the test drive results. The comparison results were obtained in Nanggalo District for Tri operator to have better network quality, which can be seen in the SINR parameter has a percentage value of 43.17% and Throughput with a percentage value of 83.56% while Telkomsel operator have a SINR value with a percentage of 17.58% and throughput with a percentage value of 36.59%.